A mosquito-eye-like superhydrophobic coating with super robustness against abrasion. (May 2021) - Liu, Jie; Zhang, Xinwen; Wang, Ruoyun; Long, Fei; Zhao, Pengyang; Liu, Lei
Abstract: Superhydrophobic coatings can offer promising protection for metals against harsh service conditions. However, real applications are facing great challenges with the focus problem of lacking mechanical robustness. Current methods addressing this issue can not completely solve the problem or is not unsuitable for large-scale applications. Here, we propose an innovative strategy to fabricate a bioinspired superhydrophobic coating on 6061 Al via a simple and high-output route. By creating a mosquito-eye-like nanoframework-nanofiller structure with two different length scales, the coating is equipped with superhydrophobic property and excellent mechanical robustness, which are usually considered as two mutually exclusive properties. Based on a modified Cassie-Baxter model and a Gibbs interfacial energy model, a wetting theory is established to analyze the observed nonlinear change of the water contact angle, which suggests that the coating initially remains in the heterogeneous wetting state and abruptly transits to the intermediate wetting state. The theory further predicts the loss of anti-icing property upon abrasion, which is also confirmed by experiments. The superhydrophobic coating with robustness against abrasion will find its potential application values in complex service conditions. Graphical abstract: Unlabelled Image Highlights: A mosquito-eye-like superhydrophobic coating with excellent robustness against abrasion is fabricated on metal surface. Variation of the superhydrophobicity with the thickness loss after abrasion is characterized using multiple techniques. The wetting performances and the evolution mechanisms of surface after abrasion are analyzed using a comprehensive model. This work provides a strategy to fabricate the robust protective coating in a large-scale, low-cost, and high-output way.